Conflict Management in Protected Areas in Turkey: Kure Mountains National Park Example - Yildiz, Damla; Atmis, Erdogan (Aves, 2023)
This study was conducted to examine the conflicts in protected areas in Turkey using the example of Kure Mountains National Park and to develop conflict management recommendations for this national park. In accordance with this purpose, the issues and the areas where conflicts were experienced, parties to the conflict, the causes and the consequences of the conflicts, and the conflict styles and strategies of the parties involved were determined. Within the scope of this study, it was revealed that there were various conflicts regarding the park's management practices, tourism activities, use of forest resources, and wildlife management processes. Most of these conflicts, both at individual and organizational levels, stem from the inadequacies of national park administration such as in the area of public relations. In order to manage the conflicts effectively, there is a need for a participatory management model that incorporates the conflicting parties.
Conflict Management in Protected Areas in Turkey: Küre Mountains National Park Example
Keywords: Bartin; Conflict Map Analysis; Conflict Tree Analysis; Forest; Kastamonu; Sustainable Forest Management